Direct Disk Diffusion Susceptibility Testing for Gram-negative Bacteria from Blood Cultures: Diagnostic Accuracy and Impact on Antimicrobial Stewardship. (4th October 2017) - Payne, Michael; Lowe, Christopher F; Leung, Victor; Romney, Marc G; Champagne, Sylvie
Abstract: Background: In order to detect multidrug resistant (MDR) bacteria, our laboratory routinely performs direct susceptibility (DS) testing from positive blood cultures. We conducted a prospective study to determine the accuracy, reporting time (RT), and antimicrobial stewardship impact of DS testing for Gram-negative bacilli (GNB) positive blood cultures. Methods: From March – December 2016, first time positive blood cultures for GNB were included in the study. Broth from positive blood culture bottles was inoculated to standard media, as well as to Mueller–Hinton agar with cefoxitin (FOX), amoxicillin/clavulanic acid (AMC), ceftriaxone (CRO), ceftazidime (CAZ), ciprofloxacin (CIP) and meropenem (MEM) disks. The CRO and CAZ were adjacent to the AMC disk, which enabled detection of zone-enhancement with extended-spectrum β-lactamase (ESBL) producing organisms. CLSI breakpoints were used to guide interpretations of the DS results. Antibiotic therapy changes, made based on verbal reporting of DS results, were recorded. In order to determine RT, the following time points were recorded: blood culture positivity, reading of DS, and reporting of standardized susceptibilities (SS). Results: There were 105 unique, monomicrobial cultures consisting of: E. coli ( N = 61), Klebsiella sp. ( N = 15), Enterobacter sp. ( N = 9), Proteus sp. ( N = 5), Pseudomonas aeruginosa ( N = 5), and 10 other miscellaneous GNB. RT was reduced from 38 to 22 hours, for SS and DS, respectively. For species with CLSI breakpoints (101 isolates), the major and minor errors for all antibiotics were 2% and 20%, respectively; 17% of isolates were DS-intermediate and SS-susceptible (minor error). CIP disk testing identified all resistant isolates correctly ( N = 21), as did MEM ( N = 7). Resistance to CRO/CAZ was correctly identified in 26/27 isolates. DS results changed antibiotic management for 23 patients. Antibiotics were narrowed for 7 patients, and treatment was expanded for 16 patients. For these patients, DS results were available 24 hours before SS. Conclusion: DS testing is an accurate and rapid method to detect MDR GNB blood culture pathogens and facilitates the optimization of antimicrobial therapy. A relatively high rate of minor errors was detected due to DS disks testing in the intermediate zone for isolates ultimately identified as susceptible by SS. Disclosures: All authors: No reported disclosures.